(untitled) (Research, Society and Development, 2024)
The Dachshund breed, popularly known as the "sausage dog," is recognized for its long body and short legs, anatomical characteristics that make it unique among canine breeds. However, these anatomical peculiarities are also associated with a series of deformities and health problems that affect the quality of life of these animals. Based on this, this work aims to describe the anatomy of Dachshunds, as well as list the main anatomical deformities these animals possess, through a literature review, correlating these characteristics with the origin of the breed. It was observed that such deformities are closely related to the history and development of the breed over the centuries. Dachshunds were originally bred in Germany for hunting badgers and other animals that live in underground burrows. To meet this purpose, these dogs were selected based on characteristics such as a long body, short legs, and a narrow chest, which allowed them to enter burrows and move easily in confined spaces. However, this artificial selection, focused on specific characteristics, resulted in significant anatomical changes that have perpetuated over generations, leading to a predisposition to various orthopedic and neurological conditions.